Multidrug Resistant Bacteria in the Respiratory Tract of Apparently Healthy Quails - Sultana, Shobnom; Islam, Md Ariful; Khatun, Mst. Minara; Nasrin, Shamima (Microbes and Health, 2013)
The study was undertaken for isolation, identification and in vitro antibiotic sensitivity assay of bacteria present in the respiratory tract of apparently healthy Japanese quails. A total of 50 samples comprised of tracheal swabs (n = 18), tracheal washings (n = 8), air sacs (n = 8), lungs (n = 8) and exudates of infraorbital sinuses (n = 8) were aseptically collected from 26 apparently healthy Japanese quails. The samples were inoculated onto a variety of media for isolation of bacteria. Identification of bacteria was performed by colony morphology, Grams staining and biochemical tests. In total, 25 (50%), 9 (18%), 22 (44%), 20 (40%) and 24 (48%) isolates were identified as Escherichia coli, Salmonella spp., Pasteurella spp., Bacillus spp. and Staphylococcus spp. respectively. Antibiotic sensitivity tests of one randomly selected isolate from each genus of bacteria were performed against 10 common antibiotics. E. coli showed resistance to four antibiotics (amoxicillin, gentamycin, nalidixic acid and tetracycline); Salmonella spp. showed resistance to seven antibiotics (amoxicillin, ampicillin, erythromycin, gentamycin, kanamycin, nalidixic acid and tetracycline); Pasteurella spp. to three antibiotics (erythromycin, sulphamethoxazole and tetracycline); Bacillus spp. to chloramphenicol and nalidixic acid and Staphylococcus spp. to amoxicillin and ampicillin. All the isolates were susceptible to ciprofloxacin. Data of this study indicate that multidrug resistant bacteria are present in the respiratory tract of clinically healthy quails. This is the first report of isolation, identification and antibiogram profile of bacteria present in the respiratory tract of quails in Bangladesh. DOI: http://dx.doi.org/10.3329/mh.v1i2.14088 Microbes and Health, 2012 1(2): 46-49